Rapid prototyping for tissue-engineered bone scaffold by 3D printing and biocompatibility study - He, Hui-Yu (Int J Clin Exp Med, 2015)
The prototyping of tissue-engineered bone scaffold (calcined goat spongy bone-biphasic ceramic composite/PVA gel) by 3D printing was performed, and the biocompatibility of the fabricated bone scaffold was studied. Pre-designed STL file was imported into the GXYZ303010-XYLE 3D printing system, and the tissue-engineered bone scaffold was fabricated by 3D printing using gel extrusion. Rabbit bone marrow stromal cells (BMSCs) were cultured in vitro and then inoculated to the sterilized bone scaffold obtained by 3D printing. The growth of rabbit BMSCs on the bone scaffold was observed under the scanning electron microscope (SEM). The effect of the tissue-engineered bone scaffold on the proliferation and differentiation of rabbit BMSCs using MTT assay. Universal testing machine was adopted to test the tensile strength of the bone scaffold. The leachate of the bone scaffold was prepared and injected into the New Zealand rabbits. Cytotoxicity test, acute toxicity test, pyrogenic test and intracutaneous stimulation test were performed to assess the biocompatibility of the bone scaffold. Bone scaffold manufactured by 3D printing had uniform pore size with the porosity of about 68.3%. The pores were well interconnected, and the bone scaffold showed excellent mechanical property. Rabbit BMSCs grew and proliferated on the surface of the bone scaffold after adherence. MTT assay indicated that the proliferation and differentiation of rabbit BMSCs on the bone scaffold did not differ significantly from that of the cells in the control. In vivo experiments proved that the bone scaffold fabricated by 3D printing had no acute toxicity, pyrogenic reaction or stimulation. Bone scaffold manufactured by 3D printing allows the rabbit BMSCs to adhere, grow and proliferate and exhibits excellent biomechanical property and high biocompatibility. 3D printing has a good application prospect in the prototyping of tissue-engineered bone scaffold.